Minimally invasive measurement of orbital compartment pressure and implications for orbital compartment syndrome: a pilot study - Enz, Tim J.; Papazoglou, Anthia; Tappeiner, Christoph; Menke, Marcel N.; Benitez, Benito K.; Tschopp, Markus (Graefe's archive for clinical and experimental ophthalmology, 2021)
Background Diagnosis of orbital compartment syndrome is mainly based on clinical findings, such as intraocular pressure and proptosis, which try to estimate the orbital compartment pressure. However, the reliability of these surrogates is unclear. Current techniques for the direct measurement of orbital compartment pressure are widely experimental and impractical in the clinical setting. Our aim was to explore the feasibility of minimally invasive needle manometry for direct measurement of orbital compartment pressure under reproducible conditions in an in vivo model of orbital congestion. We further sought to evaluate intraocular pressure and proptosis as indicators for elevated orbital compartment pressure. Methods A total of 7 ml of mepivacaine 2% solution was injected into the orbital compartment in 20 patients undergoing cataract surgery under local anesthesia. A commercially available single-use manometer device was inserted between the syringe and the injection needle to measure the orbital compartment pressure for each milliliter of intraorbital volume increment. Additionally, intraocular pressure (subgroup A; n = 10) or axial globe position (subgroup B; n = 10) were measured. Results Needle manometry allowed for rapid and continuous measurement of orbital compartment pressure. Overall mean orbital compartment pressure increased from 2.5 mmHg pre- to 12.8 mmHg post-interventionally. Both, intraocular pressure (Spearman’s correlation coefficient rs = 0.637, p < 0.0001) and proptosis (rs = 0.675, p < 0.0001) correlated strongly with the orbital compartment pressure. Conclusions Needle manometry appears to be a feasible minimally invasive instrument to directly measure orbital compartment pressure, showing promises for a more routine application in managing orbital compartment syndrome. The results further suggest that both elevated intraocular pressure and proptosis are valuable indicators for orbital compartment syndrome.